Guinea : Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility-Staff Report and Press Release on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2002)
This paper examines Guinea-Bissau's Request for a Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF). Progress was made on the structural front, but the public enterprise restructuring and privatization program continues to experience delays. The new program focuses on maintaining macroeconomic stability and accelerating growth as prerequisites for poverty reduction. Given the authorities' commitment to the poverty reduction strategy and their consistent record in meeting their obligations to the IMF, the IMF staff supports the authorities' request for a new three-year arrangement under the PRGF.